Jancok as Verbal Art: Performing Identity, Emotion, and Cultural Resistance in Arek Suroboyo - Agus Danugroho; Rustinsyah Rustinsyah; Mohammad Adib; Tuhfatul Mubarokah Assalamah; Intan Fitri Hilza (Universitas Negeri Semarang, 2026)
This study examines jancok, a profane expression commonly employed in Surabaya, as a form of vernacular performative aesthetics embedded in everyday urban interaction. Moving beyond linguistic and semantic frameworks, the article adopts an arts-based performance approach to analyze how meaning is constituted through embodied vocal enactment, including intonation, rhythm, vocal intensity, gesture, and interactional framing. Grounded in performance studies, verbal art theory, and everyday aesthetic scholarship, jancok is conceptualized as an aesthetic event rather than a linguistic unit. The analysis draws on qualitative ethnographic fieldwork conducted across multiple interactional contexts, including informal social spaces, workplaces, street encounters, creative environments, and digital platforms. The findings indicate that jancok operates through three interrelated performative dimensions: emotional aestheticization, identity enactment, and symbolic resistance. Through stylized vocal and bodily performance, the utterance transforms affect into socially legible expression, enacts Arek identity as a situated cultural practice, and negotiates norms of politeness and hierarchy through aestheticized transgression. Its expressive efficacy is sustained by performative ambiguity, allowing the utterance to oscillate between intimacy and tension.